2020
DOI: 10.3171/2020.3.spine2035
|View full text |Cite
|
Sign up to set email alerts
|

Lower Hounsfield units on CT are associated with cage subsidence after anterior cervical discectomy and fusion

Abstract: OBJECTIVEA consequence of anterior cervical discectomy and fusion (ACDF) is graft subsidence, potentially leading to kyphosis, nonunion, foraminal stenosis, and recurrent pain. Bone density, as measured in Hounsfield units (HUs) on CT, may be associated with subsidence. The authors evaluated the association between HUs and subsidence rates after ACDF.METHODSA retrospective study of patients treated with si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
22
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
(51 reference statements)
2
22
1
Order By: Relevance
“…So, we measured the inter-spinous distance on flexion-extension lateral radiography and total pseudoarthrosis rates was 28%. This result was thought to be inferior compared to previously published result 18,21) . We thought that the main reason is absence anterior plate anchoring and excessive endplate damage during the end plate preparation.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…So, we measured the inter-spinous distance on flexion-extension lateral radiography and total pseudoarthrosis rates was 28%. This result was thought to be inferior compared to previously published result 18,21) . We thought that the main reason is absence anterior plate anchoring and excessive endplate damage during the end plate preparation.…”
Section: Discussioncontrasting
confidence: 84%
“…Recent studies have evaluated the use of HU units of the commercial bone. Wang et al 18) reported that lower preoperative CT HU values are associated with cage subsidence in single-level ACDF. Their study was similar to ours however, the following differences were noted.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the use of conventional CT examination to measure vertebral HU value is gradually applied to the cervical spine, Lee et al [ 19 ] found that the vertebral HU value can be a good alternative assessment to accurately reflect BMD in the cervical spine. Wang et al [ 29 ] reported that lower preoperative HU values of the vertebral are associated with cage subsidence in single-level ACDF. Another study reported that lumbar BMD values were significantly correlated with cervical HU values; moreover, low HU values may lead to postoperative intervertebral height reduction [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Wang et al analyzed the correlation between cage subsidence in ACDF and HU value in cervical spine. They proposed there was a negative correlation between HU value and segmental height loss at the surgical level [27]. Overall, the value of HU in lumbar spine surgeries with fusion has not been fully investigated.…”
Section: Discussionmentioning
confidence: 99%